Substrates and indolebutyric acid in the rooting of 'Xavante' blackberry minicuttings collected at two times of the year (Research, Society and Development, 2020)
Blackberry (Rubus spp.), Belonging to the group of small fruits, is a promising species for use as an ornamental plant, as it has relevant attributes in relation to the characteristics of leaves, flowers and fruits, allowing the diversification of floriculture products and fruit growing. Thus, the objective of this work was to verify an adequate substrate for its cultivation in pots, in order to facilitate its use as an ornamental plant. The mini-cuttings already rooted in black mulberry 'Xavante', were transferred to polypropylene pots of five liters, to evaluate the substrates carbonized rice husk, coconut fiber Amafibra® and the mixture of both in the development of the seedlings. At 30, 60 and 90 days, the number and length of shoots and number of flowers were evaluated. At 90 days, the root dry matter mass and the physical and chemical properties of the substrates were also evaluated. Regarding the substrates, in the first 30 days of evaluation the highest number of shoots was found in coconut fiber and in the mixture of this material with carbonized rice husk. For the length of sprouts, at 60 days, the mixture of the two residues with the highest averages stood out. In this way, coconut fiber and the mixture of coconut fiber with carbonized rice husk provided more favorable conditions for the development of 'Xavante' blackberry seedlings, aiming to be used as an ornamental plant.